Assessment Serum Level of Antibodies Igg and Igm in Aborted Women with Non-Abortive in AL-Khalis City: Penilaian Tingkat Serum Antibodi Igg dan Igm pada Wanita yang Diaborsi dengan Tidak Diaborsi di Kota AL-Khalis - Maha Falih Nazzal (Universitas Muhammadiyah Sidoarjo, 2024)
The current study, which focused on women who had abortions and those who did not, was carried out in AL-Khalis city between April 2023 and August 2023. A survey was created to gather data on every instance that was part of the research. 155 blood samples were examined using a latex test, and the age group of 26 to 30 years old had the greatest abortion rate (31.57%). At the P≤0.05 level, there are notable variations. At 64.63%, the frequency was higher in urban areas, while the middle-class category had the highest rate (87.54%), followed by housewives (60.75%). Additionally, it was shown that women who experienced a first-period miscarriage had a higher infection rate (34.46%). At a rate of 60.97%, the abortion stage was either greater in the first trimester of pregnancy. At the P≤0.05 level, there are notable variations. Out of 155 instances, nine cases (3.44%) were found to be IgM positive for aborted women. The age group of 21–25 years old had the greatest percentage (5.71%). The age group of 26–30 years old had the highest infection rate (31.57%). Out of 155 cases, 5 were found to have both IgM and IgG antibodies, representing a rate of 1.88%. The age group of 21–25 years old had the highest prevalence of abortion, at 2.85%. When the latex test was used to diagnose both abortions, the study revealed a greater percentage of IgG antibody compared to IgM antibody ratios. Keywords: IgG, aborted, non-abortive women , latex test